Constructing a logical model in school health: experience on the Lower Amazon region - Elaine Fernanda Dornelas de Souza; Maria do Carmo Souza Soares; Sueyla Ferreira da Silva dos Santos; Thais Reis Silva de Paulo; Maria Verinize Santos Brandão; Ismael Forte Freitas Júnior
ABSTRACT Objective: This experience report presents the construction of the theoretical and logic model for intervention to promote physical activity and healthy eating habits of the public schools students in the city of Parintins, Amazonas, Brazil. Method: We carried out a theoretical research and also a documentary research on the School Health Program (PSE - Programa Saúde na Escola) on the national and local level, in addition to meetings with the PSE management committee for strategic planning of the actions. Result: The municipality had no systematic structure of health practices at school. A theoretical and logical model that involved prerogatives of practice from the management of the municipality in PSE was developed. Actions to promote physical activity and healthy nutrition of primary and secondary school students were planned and promoted in schools of the PSE. Final considerations: Thus, the collective construction of this proposal contributed to the research of multi-sectoral practices related to the PSE principles and strategies, considering the particularities of the Lower Amazon context.